Voice Emotion Recognition by Mandarin-Speaking Children with Cochlear Implants. Issue 1 (7th July 2021) - Ren, Lei; Zhang, Yanmei; Zhang, Junbo; Qin, Yao; Zhang, Zhikai; Chen, Zhe; Wei, Chaogang; Liu, Yuhe
Abstract : Objectives: Emotional expressions are very important in social interactions. Children with cochlear implants can have voice emotion recognition deficits due to device limitations. Mandarin-speaking children with cochlear implants may face greater challenges than those speaking nontonal languages; the pitch information is not well preserved in cochlear implants, and such children could benefit from child-directed speech, which carries more exaggerated distinctive acoustic cues for different emotions. This study investigated voice emotion recognition, using both adult-directed and child-directed materials, in Mandarin-speaking children with cochlear implants compared with normal hearing peers. The authors hypothesized that both the children with cochlear implants and those with normal hearing would perform better with child-directed materials than with adult-directed materials. Design: Thirty children (7.17–17 years of age) with cochlear implants and 27 children with normal hearing (6.92–17.08 years of age) were recruited in this study. Participants completed a nonverbal reasoning test, speech recognition tests, and a voice emotion recognition task. Children with cochlear implants over the age of 10 years also completed the Chinese version of the Nijmegen Cochlear Implant Questionnaire to evaluate the health-related quality of life. The voice emotion recognition task was a five-alternative, forced-choice paradigm, which contains sentences spoken with five emotions (happy, angry, sad, scared, and neutral) in a child-directed or adult-directed manner. Results: Acoustic analyses showed substantial variations across emotions in all materials, mainly on measures of mean fundamental frequency and fundamental frequency range. Mandarin-speaking children with cochlear implants displayed a significantly poorer performance than normal hearing peers in voice emotion perception tasks, regardless of whether the performance is measured in accuracy scores, Hu value, or reaction time. Children with cochlear implants and children with normal hearing were mainly affected by the mean fundamental frequency in speech emotion recognition tasks. Chronological age had a significant effect on speech emotion recognition in children with normal hearing; however, there was no significant correlation between chronological age and accuracy scores in speech emotion recognition in children with implants. Significant effects of specific emotion and test materials (better performance with child-directed materials) in both groups of children were observed. Among the children with cochlear implants, age at implantation, percentage scores of nonverbal intelligence quotient test, and sentence recognition threshold in quiet could predict recognition performance in both accuracy scores and Hu values. Time wearing cochlear implant could predict reaction time in emotion perception tasks among children with cochlear implants. No correlation was observed between the accuracy score in voice emotion perception and the self-reported scores of health-related quality of life; however, the latter were significantly correlated with speech recognition skills among Mandarin-speaking children with cochlear implants. Conclusions: Mandarin-speaking children with cochlear implants could have significant deficits in voice emotion recognition tasks compared with their normally hearing peers and can benefit from the exaggerated prosody of child-directed speech. The effects of age at cochlear implantation, speech and language development, and cognition could play an important role in voice emotion perception by Mandarin-speaking children with cochlear implants.